2013
DOI: 10.1002/hyp.9802
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics and recurrence analysis of extreme precipitation for observed and general circulation model generated climates

Abstract: A statistical framework based on nonlinear dynamics theory and recurrence quantification analysis of dynamical systems is proposed to quantitatively identify the temporal characteristics of extreme (maximum) daily precipitation series. The methodology focuses on both observed and general circulation model (GCM) generated climates for present (1961–2000) and future (2061–2100) periods which correspond to 1xCO2 and 2xCO2 simulations. The daily precipitation has been modelled as a stochastic process coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Traditionally, studies on weather and climate extremes have mostly focused on the extremes from a single process or variable, such as heavy precipitation or maximum temperature. For example, a multitude of studies have shown increases in the severity, duration, and frequency of precipitation and temperature extremes [4,[16][17][18][19][20][21]. The extreme value theory (EVT) constitutes the basis for statistical modeling of univariate extremes in this regard, which can generally be achieved with the probability distribution of individual extremes, such as generalized extreme value (GEV) distribution or generalized Pareto distribution (GPD) based on the annual maxima or peak over threshold [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, studies on weather and climate extremes have mostly focused on the extremes from a single process or variable, such as heavy precipitation or maximum temperature. For example, a multitude of studies have shown increases in the severity, duration, and frequency of precipitation and temperature extremes [4,[16][17][18][19][20][21]. The extreme value theory (EVT) constitutes the basis for statistical modeling of univariate extremes in this regard, which can generally be achieved with the probability distribution of individual extremes, such as generalized extreme value (GEV) distribution or generalized Pareto distribution (GPD) based on the annual maxima or peak over threshold [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…We use Recurrence Plot (RP) and the Recurrence Quantitative Analysis (RQA) methods that were developed for nonlinear analysis of temporal series, by visualizing the recurrences and calculating different complexity measures (Marwan, Romano, Thiel & Kurths, 2007). These methods were widely Research, Society and Development, v. 9, n. 9, e637997737, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7737 5 used in physiology (Afsar, Tirnakli & Marwan, 2018), geophysics (Donner et al, 2019), climatology (Panagoulia & Vlahogianni, 2014) and finances (Bastos & Caiado, 2011). We apply RP and RQA on monthly time series recorded during the period from 1962 to 2012, in three representative stations, in order to compare characteristics of rainfall regime in Zona da Mata, Agreste and Sertão.…”
Section: Santos 2019)mentioning
confidence: 99%
“…In this study, the threshold is taken as > 5σ. Recurrence plots and recurrence quantification analysis have been employed in several climate studies (Panagoulia and Vlahogianni 2014).…”
Section: Recurrence Quantification Analysis (Rqa)mentioning
confidence: 99%
“…where i , || • || ,θ are the threshold for distance, Euclidean norm and Heaviside function respectively (Panagoulia and Vlahogianni 2014). Recurrence plots have small scale structures which can be used to quantify complexity.…”
Section: Hurst Exponentmentioning
confidence: 99%